Thermal oscillations provoke physiological and biochemical changes on wheat plants infected by Pyricularia oryzae - Silva, Bruno do Nascimento (2019)
Wheat blast, caused by Pyricularia oryzae, is the most important wheat disease nowadays. High temperatures, as a consequence of climatic changes, can potentially cause physiological and biochemical changes on plants by altering their resistance to diseases. This study aimed to determine whether thermal oscillations could cause physiological and biochemical changes on wheat plants when infected with P. oryzae. Plants were submitted to different thermal acclimations (19°C and 28°C) for five days before being inoculated with P. oryzae. After inoculation, plants were kept at 25°C for 24 h and then either transferred to the initial temperature conditions or transferred to different temperature combinations (19oC→28°C and 28°C→19°C) during three days. Non-inoculated plants were submitted to these same conditions. Blast development was reduced on plants submitted to thermal acclimatization of 19oC→19oC compared to plants exposed to 28°C→28°C. There was no significant difference for blast severity between the thermal acclimations of 19oC→28°C and 28°C→19°C. Plants submitted to 28°C before or after inoculation showed impairments on photosynthesis with lower values for maximum photosystem PSII photochemical efficiency and effective PSII quantum yield, but high values for quantum yield of non-regulated energy dissipation besides lower concentration of pigments, reduction on stomatal conductance and an increase in the internal CO 2 concentration. There was high superoxide dismutase and lower ascorbate peroxidase activities for inoculated plants submitted to thermal acclimatization of 28°C→28°C. Low and high concentrations of superoxide anion and hydrogen peroxide, respectively, occurred for inoculated plants acclimated at 28°C→28°C. High chitinase, phenylalanine ammonia-lyase, and peroxidase activities occurred for inoculated plants acclimated at 28°C→28°C and 19°C→28°C. Polyphenoloxidase activity was lower for inoculated plants submitted to 28°C after or before fungal inoculation. Lipoxygenase increased on inoculated plants exposed at thermal acclimatization of 19oC→19oC. The malondialdehyde concentration was high for inoculated plants submitted to 28°C after or before fungal inoculation. In conclusion, blast development was favored on plants pre-acclimated at 28°C before fungal inoculation and kept at this same temperature during fungal infection process. By contrast, blast development was quite similar on plants pre-acclimated at 19 and 28°C before inoculation with P. oryzae and submitted, respectively, to temperatures of 28 or 19°C after inoculation. Wheat plants exposed at 28°C during the fungal infection process showed damage to the photosynthetic apparatus, a less efficient antioxidative system, and a minor contribution of the enzymes related to host defense. Key words: Defense enzymes. High temperatures. Host resistance. Photosynthesis. Wheat blast